2018
DOI: 10.1038/s41598-018-20848-6
|View full text |Cite
|
Sign up to set email alerts
|

Insights into RNAi-based antiviral immunity in Lepidoptera: acute and persistent infections in Bombyx mori and Trichoplusia ni cell lines

Abstract: The control of viral infections in insects is a current issue of major concern and RNA interference (RNAi) is considered the main antiviral immune response in this group of animals. Here we demonstrate that overexpression of key RNAi factors can help to protect insect cells against viral infections. In particular, we show that overexpression of Dicer2 and Argonaute2 in lepidopteran cells leads to improved defense against the acute infection of the Cricket Paralysis Virus (CrPV). We also demonstrate an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…Viruses 2020, 12, x; doi: FOR PEER REVIEW www.mdpi.com/journal/viruses A previous study by our group revealed that pathogenic infection of lepidopteran Bm5 cells and dipteran S2 cells with CrPV occurred with different kinetics [11]. While in S2 cells cytopathic effects became evident already after 36-48 h, pathogenicity in Bm5 cells was observed only after 2-3 weeks.…”
Section: Viruses 2020 12 X For Peer Review 4 Of 18mentioning
confidence: 89%
See 2 more Smart Citations
“…Viruses 2020, 12, x; doi: FOR PEER REVIEW www.mdpi.com/journal/viruses A previous study by our group revealed that pathogenic infection of lepidopteran Bm5 cells and dipteran S2 cells with CrPV occurred with different kinetics [11]. While in S2 cells cytopathic effects became evident already after 36-48 h, pathogenicity in Bm5 cells was observed only after 2-3 weeks.…”
Section: Viruses 2020 12 X For Peer Review 4 Of 18mentioning
confidence: 89%
“…However, in order to link the host specific metabolic changes to viral pathogenesis, it will be necessary to conduct further studies in different host cells where comparable infection kinetics are observed. For example, although S2 cells are more sensitive than the other cell lines that were investigated, the kinetics of infection in Hi5 cells can be considerably accelerated after application of CrPV at much higher MOI [11]. Thus, comparative metabolomics studies could be extended between pathogenically infected S2 and Hi5 cells as well as among several other persistently infected lepidopteran and coleopteran cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these do not always cause obvious pathogenesis, their existence is often neglected. However, recently, identification of persistent viruses in insects has become recurring, with several reported cases both in vivo and in cultured cells (Katsuma et al, 2005; Habayeb et al, 2006; Li et al, 2007; Wu et al, 2010; Jovel and Schneemann, 2011; Iwanaga et al, 2012; Ma et al, 2014; Suzuki et al, 2015; Swevers et al, 2016; Santos et al, 2018). Interestingly, whether an infection is persistent or acute does not depend only on the virus itself, but also on the host.…”
Section: Insect Viral Infections and Rnai-based Antiviral Immunitymentioning
confidence: 99%
“…Interestingly, whether an infection is persistent or acute does not depend only on the virus itself, but also on the host. As demonstrated by several loss-of-function and deep sequencing studies, the role of RNAi in the established equilibrium between the persistent virus and the insect host is clear (Wu et al, 2010; Goic et al, 2013; Zografidis et al, 2015; Petit et al, 2016; Santos et al, 2018). However, the possible role of still unidentified factors has to be considered.…”
Section: Insect Viral Infections and Rnai-based Antiviral Immunitymentioning
confidence: 99%